Analisis Monitoring dan Evaluasi Kinerja Dosen Berdasarkan Penilaian Mahasiswa - Nurfaidah, Wardah; Aprilda, Risma; Kholik, Abdul; Mahnun, Nunu (Fakultas Tarbiyah dan Keguruan, 2024)
This research aims to determine the results of monitoring and evaluation analysis of lecturer performance based on student assessments at the Al-Ikhlas Nursing Academy. The method used in this research is quantitative, collecting data through questionnaires with incidental sampling techniques. The data analysis used is quantitative descriptive analysis using the formula calculation . The results of the analysis show that students are satisfied with the performance of educators or lecturers and the performance criteria for lecturers are in good criteria with an average score of 67,40. Meanwhile, the highest score from the analysis results was in the Empathy aspect with an average score of 72,15 and the lowest score was in the Responsiveness aspect with a score of 60,77. This means that the majority of students at the Al-Ikhlas Nursing Academy are satisfied with the performance of educators and the performance criteria for educators are in the good performance category. So efforts are needed to continue to optimize it so that the performance of educators at the Al-Ikhlas Nursing Academy is of higher quality.